PROGNOSTIC FACTORS AND LONGTERM SURVIVAL OF MYOCARDIAL INFARCTION PATIENTS, COMPLICATED BY EARLY RECURENT ANGINA AND RENAL FUNCTION DECREASE - N. R. Khasanov; O. S. Belkorey; E. N. Dyakova (Российский кардиологический журнал)
Aim. To study prognosis factors for early postinfarction angina (EPA) in myocardial infarction (MI) and decreased functioning of kidneys, and long-term survival in this group of patients.Material and methods. Into the retrospective study, 179 patients included, of hospitalized to Moscow clinics, with verified diagnosis MI. Decreased kidney function was defined as GFR <59 mL/min/1,73 m2 . The endpoint was death and complications during hospitalization and all follow up. Time mediana was 18 months.Results. Totally, 29 cases registered (17,4%) of EPA in MI and known GFR (n=167). Patients with EPA were significantly older (72±11 y. and 62±12 y., respectively, р=0,0001) and among those males predominated (p=0,001). Atrial fibrillation (AF) and diabetes (DM) among EPA patients were significantly more prevalent. In decreased renal function group, EPA was found in 45,5 (n=25), in normal GFR — in 3,5% (n=4, p=0,0001), and the risk of EPA in decreased GFR below 59 mL/ min/1,73 m2 increased 14 times (RR=13,9; 95% CI=4,23-45,65; p=0,001). Long term mortality in EPA group was 30,8% (p=0,001).Conclusion. PCI improved survival rate in EPA and decreased renal function patients.